Estetyzacja – nowa matryca kultury - Guzowska, Beata (Człowiek i Społeczeństwo, 2015)
Aestheticization surely there is important trend of modern culture techniques of forming of bodies including, personalities and manners of visions and reasoning of cultural-socially reality. Full endures existing between art distribution life daily earlier aestheticization but daily life. Mass media, consumption, promote new pattern (sample) advertising homo aestheticus. Homo aestheticus, it certain kind matrix, which (who) defines modern unit impermanence characterizing, imperfection, improvisation, as well as have to create. Esthetic experience includes various areas of our lives be determinant getting (reach) conversion and more and more matrix of modern culture significant.